PHYSICAL CHARACTERIZATION OF POLYURETHANECLAY COMPOSITE DOPED WITH TREATED AND UNTREATED PU WASTE AS FILLER FOR SUBGRADE LAYER APPLICATIONS - Aida Atiqah Atil, Aida Atiqah Atil; Nik Normunira Mat Hassan, Nik Normunira Mat Hassan; Adyla Illyana Roseli, Adyla Illyana Roseli; Fatimah Mohamed Yusop, Fatimah Mohamed Yusop; Anika Zafiah Mohd Rus, Anika Zafiah Mohd Rus; Noraini Marsi, Noraini Marsi; Tuan Noor Hasanah Tuan Ismail, Tuan Noor Hasanah Tuan Ismail; Nur Faezah Yahya, Nur Faezah Yahya (2023)
One of the most efficient ways to enhance the geotechnical characteristics of soils is to use polyurethane waste as a filler. In this study, the PU waste was soaked in a 0.05 M sodium hydroxide (NaOH) solution as an alkaline cleaner before being sieved to a size of 300 m. Then, the PU waste as filler was dried in microwaves and a drying oven. The PU clay composite samples were prepared at 0%, 2.5%, and 5% of PU waste filler loading namely PU waste untreated (PU-CCUn), PU waste treated by microwave (PU-CCTW), and PU waste treated by the oven (PU-CCTO), respectively. Fourier Transform Infrared spectroscopy (FTIR), scanning electron microscopy (SEM), and water absorption was used to examine the physical characteristics of PU clay composite with treated and untreated PU waste filler loading. According to the results, the functional group of PU clay composite samples shows no significant changes with the drying treatment. However, from SEM image exhibited the PU waste particle was mixed successfully in clay. The PU clay composite shows that 12% more water was absorbed by PU-CCUn than by PU-CCTO and PU-CCTM due to the bigger pore sizes. In summary, the risk of overheating and burning the PU waste as filler powder with the microwave processing method makes the prospective PU-CCTO the best potential in comparison to PU-CCUn and PU-CCTM. This demonstrated the effectiveness of the drying oven treatment method and its superior wettability to that of the microwave. In the future, it is recommended to utilize PU waste as filler that has been dried at a variable ratio of up to 10%.